Pengaruh Kepemimpinan Transformasional, Disiplin Kerja, dan Motivasi Kerja Terhadap Kinerja Karyawan Pada PT. Aragon Tambang Pratama - Kahananto, Kahananto; Lahindah, Laura (Green Publisher Indonesia, 2025)
This study aims to analyze the influence of transformational leadership, work discipline, and work motivation on employee performance at PT. Aragon Tambang Pratama. The research employed a quantitative approach with causal associative design involving 59 respondents from the operational division. Data were collected through Likert scale questionnaires and analyzed using multiple linear regression. Results indicate that transformational leadership has a significant positive effect on employee performance (β=0.098, p=0.019). Work discipline proved to be the most dominant variable with highly significant influence (β=0.910, p=0.000). Conversely, work motivation does not significantly affect employee performance (β=-0.013, p=0.475). Simultaneously, all three variables significantly influence employee performance with F=1183.656 (p=0.000). The research model explains 98.4% of employee performance variation (Adjusted R²=0.984). These findings indicate that in the mining industry context, work discipline becomes a key determining factor of performance, followed by transformational leadership, while work motivation does not contribute significantly. Practical implications emphasize the importance of developing effective work discipline systems and strengthening transformational leadership capacity to sustainably improve employee performance. The study provides valuable insights for management in identifying performance-influencing factors and developing appropriate strategies in the mining industry context.